Role of Laboratory Services as Support of Health Care (Bangladesh Journal of Medical Science, 2014)
DOI: http://dx.doi.org/10.3329.bjms.v1i3.17911Bangladesh Journal of Medical Science Vol.1(3) 1994 pp.25-27